Evaluasi Strategi Pengembangan Budidaya Ikan (Sambang Budiman) Pada UPT Budidaya Perikanan Air Tawar (BPAT) Ngoro Kabupaten Jombang - Kiswanto, Arizal; Rahaju, Tjitjik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by the efforts of the Fisheries Production Sector in optimizing the role and complementing the duties of the UPT BPAT Ngoro owned by the Food Security and Fisheries Service of Jombang Regency as a center of education (COE) for the community. Because before this program was inaugurated, the UPT was still limited in terms of education and only carried out the institutional duties to produce quality fish seeds for farmers. The aim is to evaluate and analyze the policy of the fish cultivation development strategy program (Sambang Budiman) at the UPT Freshwater Fisheries Cultivation (BPAT) Ngoro, Jombang Regency using a formal retrospective evaluation model according to William N Dunn (2003) with 6 indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The research findings show that the performance results of the four activities of the Sambang Budiman program have succeeded in making UPT BPAT Ngoro a fisheries education institution, but there are still structural challenges such as the limited adequacy of fisheries education house activities in reaching students, responsiveness through the distribution of beneficiary results after participating in technical guidance activities, and inequality in human resource efficiency in fish seed production. The input given is more attention from the implementer's disposition in highlighting potential gaps in activities in the Sambang Budiman program that have been realized.